Success: the synergy of off-pump coronary artery bypass and living donor liver transplantation—a two-case report - Yazici, Sinan Efe; Atasever, Ahmet; Cetinarslan, Ozge; Turan, Ebru; Sagbas, Ertan; Yuzer, Yıldıray (Frontiers in Surgery, 2025)
BackgroundEnd-stage liver disease (ESLD) patients frequently exhibit comorbid coronary artery disease (CAD), complicating liver transplantation (LT) due to increased perioperative cardiovascular risk. In patients for whom percutaneous coronary intervention (PCI) is not feasible, coronary artery bypass grafting (CABG) may be required prior to or during LT. Off-pump CABG (OPCAB) presents a promising strategy to minimize the hemodynamic and inflammatory burdens associated with cardiopulmonary bypass, especially in ESLD patients undergoing major surgery.Case presentationsWe present two male patients (aged 60 and 61) with ESLD and significant LAD stenosis who underwent simultaneous OPCAB and living donor liver transplantation (LDLT). The first case involved cryptogenic cirrhosis and recurrent variceal bleeding; the second had HBV/HDV-related cirrhosis and hepatocellular carcinoma. In both cases, OPCAB was performed using the left internal mammary artery (LIMA) graft on a beating heart. Subsequently, LDLT was carried out using standard piggy-back techniques. Portal pressure modulation via splenic artery ligation was performed in the first case due to elevated post-reperfusion portal flow. Anesthetic management emphasized hemodynamic monitoring and stability. Both patients were extubated on postoperative day one, discharged with triple immunosuppression, and followed for 6–12 months with preserved cardiac and graft function. A bile leak from the cystic duct anastomosis was encountered in one case.ConclusionSimultaneous OPCAB and LDLT is a feasible and safe approach in carefully selected ESLD patients with CAD when performed by experienced multidisciplinary teams. Avoiding PCI mitigates bleeding risks associated with dual antiplatelet therapy, while OPCAB circumvents the deleterious effects of cardiopulmonary bypass. This strategy may shorten transplant wait times and optimize both cardiac and hepatic outcomes in high-risk populations.